1988
DOI: 10.1002/j.1939-4640.1988.tb01034.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pituitary‐Testicular Axis at Rest and During Moderate Exercise in Males with Diabetes Mellitus and Normal Sexual Function

Abstract: Hormonal studies of pituitary-testicular function in insulin-dependent diabetes mellitus were examined at rest and during moderate exercise to assess whether diabetes per se caused abnormalities of nocturnal penile tumescence and androgen function in men with normal sexual function. The present study compared 10 healthy men and eight men with Type I diabetes mellitus in whom normal sexual function was determined by clinical history. Urinary gonadotropin excretion, semen analysis and diurnal variation of serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Freetestosterone plasma levels are lower in impotent diabetics than in those who are not impotent or in normal men [3, 6, 271. These findings have not been confirmed [28,35,391.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Freetestosterone plasma levels are lower in impotent diabetics than in those who are not impotent or in normal men [3, 6, 271. These findings have not been confirmed [28,35,391.…”
Section: Introductionmentioning
confidence: 78%
“…The response of FSH to stimulation with exogenous gonadatropin-releasing hormone (GnRH) in diabetic subjects may be normal [7,9,11,14,32, 391, below normal [41], or exaggerated [20,241. A normal response of LH to stimulation with exogenous GnRH has been reported [14, 321, as has a decreased response [2, 9, 35, 39, 411. Plasma testosterone concentrations are similar to [2,14,19,20,24,28,31,39, 401 or lower than [15, 31 those in normal men. The response of testosterone to human chorionic gonadotropin (hCG) may be normal [lo] or below normal [2, 141.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Testosterone levels were shown to be low in men with diabetic ketoacidosis and rose with recovery, presumably secondary to the effects of a severe illness (Semple et al, 1988). A study comparing healthy type 1 diabetic men with normal controls all of whom had no reported sexual dysfunction, showed that there were no significant differences between the two groups in terms of pituitary-testicular axis during moderate exercise and at rest (Murray et al, 1988). An association between low testosterone levels and insulin resistance in type 2 diabetes has been suggested and insulin levels have been shown to correlate inversely with testosterone levels in men with diabetes (Andersson et al, 1994).…”
Section: Diabetesmentioning
confidence: 99%